Evaluating ESG corporate performance using a new neutrosophic AHP-TOPSIS based approach - Reig-Mullor, Javier; Garcia-Bernabeu, Ana; Pla-Santamaria, David; Vercher-Ferrandiz, Marisa (Technological and Economic Development of Economy, 2022)
Corporate sustainability reports’ credibility of environmental, social, and governance (ESG) information has received a significant focus of attention in the businesses landscape. Over the last years, various methodologies and multicriteria approaches have been developed to assess the ESG performance of companies. To consider the uncertainty that arises from imprecision and subjectivity in evaluating ESG criteria, this paper proposes to develop a novel hybrid methodology that combines AHP and TOPSIS techniques under a neutrosophic environment. We test the suggested proposal through a real case study of the leading companies in the oil and gas industry. Moreover, we conduct a sensitivity analysis for evaluating any discrepancies in the ranking due to using different fuzzy numbers and weighting vectors.First published online 05 July 2022